Meeting the short term social debt: the case of Trinidad and Tobago: background paper - Pantin, Dennis A. (ILO. PREALC Caribbean Office Port of SpainTT, 1991)
Studies the social debt situation in Trinidad and Tobago within the conceptual and methodological framework of pioneering work of PREALC in this area. Details the build up of foreign indebtedness and the onset of 'external surveillance' by the IMF and World Bank and measures the impact of short term social debt on social groups in Trinidad and Tobago. Advances proposals for repayment of the social debt within an equitable adjustment process.